The Tasawur of Mahabbah According to Bediuzzaman Said Nursi Based on The Book of Kulliyyat Rasa'il Al-Nur - Norullisza Khosim; Mohd Shukri Hanapi (Universiti Sultan Zainal Abidin (UNISZA), 2024)
Vol 24 No 1